The implementation of cooperative learning model on student activity in learning social studies in elementary school - Arneeta Paquita Bachtiar; Ali Sunarso (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to explore the implementation of the cooperative learning model and its influence on student activity and learning outcomes in Social Studies (IPS) for sixth-grade students at SD Negeri 1 Tambakrejo, Kendal Regency. The background of this study arises from the low student participation in IPS learning, which is still dominated by conventional, one-way teaching methods. This qualitative research employed a case study design involving one classroom teacher and 25 students. Data collection techniques included observation, semi-structured interviews, documentation, and student learning outcome tests. The data were analyzed using the interactive model by Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The results show a significant increase in student activity after implementing the cooperative learning model. Observations indicated that indicators such as asking questions, engaging in group discussions, and presenting results improved substantially. Interviews revealed enhanced student motivation, confidence, and social interaction. Furthermore, the average student score increased from 71.2 to 81.6 after implementation. These findings suggest that the cooperative learning model not only fosters active learning but also positively affects students’ academic performance. This model is recommended as an alternative approach to improve student engagement in elementary Social Studies education.